The power of energy‐resolved tandem mass spectrometry experiments for resolution of isomers: the case of drug plasma stability investigation of multidrug resistance inhibitors. (29th December 2015) - Menicatti, Marta; Guandalini, Luca; Dei, Silvia; Floriddia, Elisa; Teodori, Elisabetta; Traldi, Pietro; Bartolucci, Gianluca
Abstract : Rationale: A series of drug plasma stability experiments were carried out to evaluate the bioavailability of three multidrug resistance inhibitors. The studied compounds are positional isomers; therefore, a chromatographic separation or taking advantage of specific collisionally activated decomposition pathways, obtained by tandem mass spectrometry (MS/MS) experiments, is necessary in order to resolve them. Methods: A method was developed for quantitative determination of the analytes in plasma using liquid chromatography (LC) coupled with a triple quadrupole mass spectrometer operating in MS/MS mode. Different collisional approaches were employed based on the potentiality of a triple quadrupole system. Aside from the classical product ion spectroscopy, energy‐resolved MS/MS experiments and a post‐processing mathematical algorithm tool (LEDA) were used to distinguish among different kinds of inhibitors present in the sample batch. Results: The developed LC/MS/MS method showed precision between 1.8–7.9%, accuracy ranging from 92.8 to 99.9% and limit of detection (LOD) values in the range 1.0–1.4 ng mL −1 for all the analytes. The evaluation of matrix effects demonstrated that the sample preparation procedure did not affect the ionization efficiency or recovery (matrix effects and recovery larger than 88%). Finally, the LEDA tool was able to differentiate among the isomers, ensuring their proper monitoring. Conclusions: The proposed LC/MS/MS method was suitable for evaluating the stability of the analytes in plasma samples, although small concentration variations occurred. Furthermore, the investigation on the energetics of fragmentation pathways allowed the better product ions and optimal abundance ratios to be selected for LEDA application into a multi‐component analysis. Copyright © 2015 John Wiley & Sons, Ltd.